Diagnostic Interviewing - Hersen, Michel; Turner, Samuel M. (New York, NY Springer US, 2003)
Almost two decades have passed since the publication of the first edition of this acclaimed text. The new third edition carries on the tradition of the previous two in offering a practical, state of the art presentation of the interview process. The critical first step to diagnosis and treatment, the interview is as much art as science, and this text provides a wealth of material to enhance clinical skill as well as empirically-derived foundations. The structure of the text has been retained, with chapters by noted experts detailing current innovations in theory and practice, including recent changes to the DSM-IV. Completely revised and updated, accessible, and illustrated with relevant case material, the third edition of Diagnostic Interviewing will be a welcome text for instructors and students, as well as a valuable resource for clinicians
I. General Issues -- 1. The Interviewing Process -- 2. Mental Status Examination -- 3. Interviewing Strategies -- 4. Consideration of Neuropsychological Factors in Interviewing -- II. Specific Disorders -- 5. Anxiety Disorders -- 6. Mood Disorders -- 7. Schizophrenia -- 8. Personality Disorders -- 9. Alcohol Problems -- 10. Drug Abuse -- 11. Sexual Dysfunctions and Deviations -- 12. Eating Disorders -- 13. Psychophysiological Disorders -- 14. Post-Traumatic Stress Disorder (Combat) -- 15. Post-Traumatic Stress Disorder (Noncombat) -- III. Special Populations -- 16. Marital Dyads -- 17. Children -- 18. Sexually and Physically Abused Children -- 19. Older Adults
Keywords: Social service; Clinical psychology; Clinical health psychology; Health Psychology; Clinical Psychology; Psychiatry; Social Work